Avaliação do efeito citotóxico da lectina da esponja marinha Cliona varians contra células de leucemia mielóide crônica - Moura, Gioconda Emanuella Diniz de Dantas (2007)
In this study, a BCR-ABL expressing human chronic myelogenous leukaemia cell line (K562) was used to investigate the antitumoral potential of a novel lectin (CvL) purified from the marine sponge Cliona varians. CvL inhibited the growth of K562 cells with an IC50 value of 70 g/ml, but was ineffective to normal human peripheral blood lymphocytes in the same range of concentrations tested (180 g/ml). Cell death occurred after 72 h of exposure to the lectin and with sign of apoptosis as analysed by DAPI staining. Investigation of the possible effectors of this process showed that cell death occurred in the presence of Bcl-2 and Bax expression, and involved a caspase-independent pathway. Confocal fluorescence microscopy indicated a major role for the lysosomal protease cathepsin B in mediating cell death. Accordingly, pre-incubation of K562 cells with the cathepsin inhibitor L-trans-epoxysuccinyl-L-leucylamido-(4-guanidino)butane (E-64) abolished the cytotoxic effect of CvL. Furthermore, we found upregulation of tumor necrosis factor receptor 1 (TNFR1) and down-modulation of p65 subunit of nuclear factor kappa B (NFB) expression in CvL-treated cells. These effects were accompanied by increased levels of p21 and downmodulation of pRb, suggesting that CvL is capable of cell cycle arrest. Collectively, these findings suggest that cathepsin B acts as death mediator in CvL-induced cytotoxicity possibly in a still uncharacterized connection with the membrane death receptor pathway